Penguatan Pemanfaatan Tanaman Obat Keluarga bagi Peningkatan Kesehatan Warga Bukit Sangkal - Novianti, Rahmi; Indah Pusnita; Yana Mahdiana; Solihin; Firza Juita (LPPM UNINUS, 2025)
One of the public health issues in Bukit Sangkal, Palembang, is the underutilization of local resources such as Family Medicinal Plants (TOGA). The local community lacks awareness about the benefits of TOGA and has yet to optimize its cultivation and use in daily life. This community service program aims to empower residents through education and training on TOGA cultivation, utilization, and management as an alternative solution to support family health. The methods used include participatory counseling, hands-on field training, and ongoing assistance for residents of RT 30. The results show an increase in community knowledge and skills in cultivating and using TOGA. Several households have also begun independently managing TOGA in their home environments. Additionally, this activity produced educational outputs such as a simple TOGA handbook and short tutorial videos for sustainable use. In conclusion, TOGA empowerment in Bukit Sangkal has proven effective in promoting community health based on local potential. Keywords: TOGA, community health, empowerment, community service, medicinal plants